Cultural effects on inbound tourism into the USA: a gravity approach - Christoph Vietze (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
In this paper we discuss the effects of cultural and particular religious factors on tourist flows into the USA as the world largest tourism destination. To estimate this empirically we run an augmented gravity equation. Our results give evidence that the gravity equation is an adequate instrument to explain variations in international tourist flows. With respect to the aim of the paper, we have found that cultural proximity between country of origin and country of destination have positive effects on the tourism flows between these countries. In particular, after controlling for a set of geographic variables, people from countries with the same language (English) and the same high governmental rankings like the USA, travel more into the USA for holiday than people from other countries. Above all, we have clear and stable evidence that tourists from Christian countries prefer the USA as holiday destination much stronger than people from other countries. This supports our argument that people wishing to go on holiday to countries with a similar cultural and political background.
Keywords: F14; L83; Z12; 330; Tourism; cultural factors; religion; Tourismus; Ausländisch; Urlaubsverhalten; Kulturpsychologie; Religion; USA